Effect of Paternal Blue Catfish Strain Effects on Hatchery Fry Production and Performance of Channel Catfish × Blue Catfish F1 Hybrid Fry Production and Fingerling Performance Under Commercial Conditions. (15th August 2016) - Chatakondi, Nagaraj G.; Yant, Roger D.; Dunham, Rex A.
Abstract: This study examined the influence of strain of sire on hybrid catfish embryo production and performance of fingerlings under commercial conditions. Four hundred 4‐year‐old female Gold Kist strain Channel Catfish Ictalurus punctatus were induced to spawn in eight spawning trials. The stripped eggs were fertilized with the sperm of either D&B or Rio Grande Blue Catfish I. furcatus to produce D&B or Rio Grande hybrid catfish embryos. Testes weight (g/kg body weight [BW]) was higher in Rio Grande (1.98 ± 0.28 g/kg BW) than in D&B (1.02 ± 0.12 g/kg BW) Blue Catfish males. Hatching parameters between Rio Grande and D&B hybrids did not differ. Approximately 100, 000 hybrid catfish fry produced from each spawning trial were stocked in an individual 0.4‐ha pond to raise fingerlings. Four ponds of D&B and four ponds of Rio Grande hybrids were stocked in eight ponds of identical conditions at the same time. The mean individual BW of D&B hybrid fingerlings (38.5 g) was higher than that of Rio Grande hybrid fingerlings (32.5 g) at 9 months of age. Mean survival (99.3%), production (8, 875 kg/ha), and feed conversion (1.14) of D&B hybrid catfish fingerlings were superior to Rio Grande hybrid catfish fingerling survival (92.1%), production (7, 664 kg/ha), and feed conversion (1.23), the catfish being raised in replicated earthen ponds under farm conditions. While the D&B strain of sire improved the performance of hybrid catfish fingerlings, it had minimal influence on hybrid catfish fry production.